Effects of Sub-soil Drip Fertigation on Sugarcane in Field Conditions - Gui-Fen Chen; Qi-Zhan Tang; Yang-Rui Li; Yu-Yi Huang; Bin Liu; Lin Xu; Hai-Rong Huang (Sugar Tech, 2012)

Exogenous hydrogen sulfide attenuates diabetic myocardial injury through cardiac mitochondrial protection - Xin Zhong; Leihong Wang; Yuwen Wang; Shiyun Dong; Xiaoning Leng; Jing Jia; Yajun Zhao; Hulun Li; Xinying Zhang; Changqing Xu; Guangdong Yang; Lingyun Wu; et al. (Molecular and Cellular Biochemistry, 2012)

Postconditioning with vagal stimulation attenuates local and systemic inflammatory responses to myocardial ischemia reperfusion injury in rats - Qiang Wang; Yi Cheng; Fu-Shan Xue; Yu-Jing Yuan; Jun Xiong; Rui-Ping Li; Xu Liao; Jian-Hua Liu (Inflammation Research, 2012)

Effects of warming and grazing on soil N availability, species composition, and ANPP in an alpine meadow - Shiping Wang; Jichuang Duan; Guangping Xu; Yanfen Wang; Zhenhua Zhang; Yichao Rui; Caiyun Luo; Burenbayin Xu; Xiaoxue Zhu; Xiaofeng Chang; Xiaoyong Cui; Haishan Niu; et al. (Ecology, 2012)
Uncertainty about the effects of warming and grazing on soil nitrogen (N) availability, species composition, and aboveground net primary production (ANPP) limits our ability to predict how global carbon sequestration will vary under future warming with grazing in alpine regions. Through a controlled asymmetrical warming (1.2/1.7°C during daytime/nighttime) with a grazing experiment from 2006 to 2010 in an alpine meadow, we found that warming alone and moderate grazing did not significantly affect soil net N mineralization. Although plant species richness significantly decreased by 10% due to warming after 2008, we caution that this may be due to the transient occurrence or disappearance of some rare plant species in all treatments. Warming significantly increased graminoid cover, except in 2009, and legume cover after 2008, but reduced non‐legume forb cover in the community. Grazing significantly decreased cover of graminoids and legumes before 2009 but increased forb cover in 2010. Warming significantly increased ANPP regardless of grazing, whereas grazing reduced the response of ANPP to warming. N addition did not affect ANPP in both warming and grazing treatments. Our findings suggest that soil N availability does not determine ANPP under simulated warming and that heavy grazing rather than warming causes degradation of the alpine meadows.

Association of interleukin 23 receptor gene polymorphisms (rs10489629, rs7517847) with rheumatoid arthritis in European population: a meta-analysis - Yu Zhai; Ke Xu; Fen Huang; Hui Peng; Chen-Chen Feng; Kao-Kao Zhu; Rui-Xue Leng; Hai-Feng Pan; Dong-Qing Ye (Molecular Biology Reports, 2012)

Isolation and characterization of fifteen novel microsatellite loci in golden mandarin fish (Siniperca scherzeri) Steindachne - Min Yang; Xu-Fang Liang; ChangXu Tian; Yasmeen Gul; YaQi Dou; Liang Cao; Rui Yu (Conservation Genetics Resources, 2012)

Warming and grazing increase mineralization of organic P in an alpine meadow ecosystem of Qinghai-Tibet Plateau, China - Yichao Rui; Yanfen Wang; Chengrong Chen; Xiaoqi Zhou; Shiping Wang; Zhihong Xu; Jichuang Duan; Xiaoming Kang; Shunbao Lu; Caiyun Luo (Plant and Soil, 2012)

Increased expression of calcium-sensing receptors in atherosclerosis confers hypersensitivity to acute myocardial infarction in rats - Jin Guo; Hong-zhu Li; Lu-chuan Wang; Wei-hua Zhang; Guang-wei Li; Wen-jing Xing; Rui Wang; Chang-qing Xu (Molecular and Cellular Biochemistry, 2012)

Synthesis and studies on antidepressant activity of 2′,4′,6′-trihydroxychalcone derivatives - Xin Sui; Ying-Chun Quan; Yue Chang; Rui-Peng Zhang; Yin-Feng Xu; Li-Ping Guan (Medicinal Chemistry Research, 2012)

Characterization of a spliced variant of human IRF-3 promoter and its regulation by the transcription factor Sp1 - Wei Ren; Liang-Hua Zhu; Hua-Guo Xu; Rui Jin; Guo-Ping Zhou (Molecular Biology Reports, 2012)

Synthesis of 2-R1-2-(4-(2-fluoroethoxy)benzamido)acetate as potential PET imaging agents - Yong He; Jingli Xu; Hang Liu; Man Feng; Xiao Wang; Rui Ding; Chuanmin Qi; Yurong Chen; Fang Li; Zhao-Hui Zhu; Yong-Hong Dang; Ming Wang; et al. (Medicinal Chemistry Research, 2012)

In vitro and in vivo hepatoprotective and antioxidant effects of Astragalus polysaccharides against carbon tetrachloride-induced hepatocyte damage in common carp (Cyprinus carpio) - Rui Jia; Liping Cao; Pao Xu; Galina Jeney; Guojun Yin (Fish Physiology and Biochemistry, 2012)

Gene expression profile of campylobacter jejuni-induced GBS in bama miniature pigs - Feng Xue; Dexin Zeng; Fei Xu; Rui Zhang; Yang Chen; Yuefei Yang; Xiaobo Wang; Zhenzhong Li; Xiaorong Zhang; Yuan Jiang (Cell and Tissue Research, 2012)

Synthesis of benzopyrano[4,3-b](N-arylsulfonyl)indoles and benzopyrano[3,4-b](N-arylsulfonyl)indoles via intramolecular palladium-catalyzed aryl–aryl coupling reaction - Ling-ling Fan; Zhi-ping Che; Rui Zhang; Xiang Yu; Xiao-yan Zhi; Hui Xu (Molecular Diversity, 2012)

siRNAs target sites selection of ezrin and the influence of RNA interference on ezrin expression and biological characters of osteosarcoma cells - XiFu Shang; YaoFei Wang; QiChun Zhao; KeRong Wu; Xu Li; XiaoFeng Ji; Rui He; WenZhi Zhang (Molecular and Cellular Biochemistry, 2012)

Erbin inhibits TGF-β1-induced EMT in renal tubular epithelial cells through an ERK-dependent pathway - Qiaodan Zhou; Rui Zeng; Chuou Xu; Lili Liu; Lin Chen; Pei Kou; Guangchang Pei; Shoujun Bai; Yamin Zhang; Caixia Li; Song Rong; Min Han; et al. (Journal of Molecular Medicine, 2012)

Preparation and bioevaluation of 99mTc nitrido radiopharmaceuticals with pyrazolo[1,5-a]pyrimidine as tumor imaging agents - Rui Ding; Yong He; Jingli Xu; Hang Liu; Xiao Wang; Man Feng; Chuanmin Qi; Junbo Zhang; Cheng Peng (Medicinal Chemistry Research, 2012)

Oceaniovalibus guishaninsula gen. nov., sp. nov., A Marine Bacterium of the Family Rhodobacteraceae - Keshao Liu; Rui Zong; Qipei Li; Yingnan Fu; Yongle Xu; Yanan Wang; Nianzhi Jiao (Current Microbiology, 2012)

Natural Heritage value of Xinjiang Tianshan and global comparative analysis - Xiaoliang Xu; Zhaoping Yang; Adayi Saiken; Shao Rui; Xinyu Liu (Journal of Mountain Science, 2012)

In silico identification of potential drug targets in swine pathogen Haemophilus parasuis - Zhuofei Xu; Lifang Ma; Huanchun Chen; Rui Zhou (Genes & Genomics, 2012)

Involvement of calcium-sensing receptor in oxLDL-induced MMP-2 production in vascular smooth muscle cells via PI3K/Akt pathway - Hong-Xia Li; Fan-Juan Kong; Shu-Zhi Bai; Wen He; Wen-Jing Xing; Yu-Hui Xi; Guang-Wei Li; Jin Guo; Hong-Zhu Li; Ling-Yun Wu; Rui Wang; Guang-Dong Yang; et al. (Molecular and Cellular Biochemistry, 2012)

A New Piezochromic Fluorescence and Aggregation-Induced Emission Compound Containing Tetraphenylethylene and Triphenylamine Moieties with Morphology-alterable Property - Xie Zhou; Hai-yin Li; Zhen-guo Chi; Bing-jia Xu; Xi-qi Zhang; Yi Zhang; Si-wei Liu; Jia-rui Xu (Journal of Fluorescence, 2012)

The genetic analysis of the flp locus of Actinobacillus pleuropneumoniae - Tingting Li; Zhuofei Xu; Tengfei Zhang; Lu Li; Huanchun Chen; Rui Zhou (Archives of Microbiology, 2012)

Transcriptional control of human CD2AP expression: the role of Sp1 and Sp3 - Hua-Guo Xu; Wei Ren; Li Zou; Yi Wang; Rui Jin; Guo-Ping Zhou (Molecular Biology Reports, 2012)

The short-term cover crops increase soil labile organic carbon in southeastern Australia - Xiaoqi Zhou; Chengrong Chen; Shunbao Lu; Yichao Rui; Hanwen Wu; Zhihong Xu (Biology and Fertility of Soils, 2012)

Type 17 T-helper cells might be a promising therapeutic target for osteoporosis - Feng-Lai Yuan; Xia Li; Wei-Guo Lu; Yi-Qing Zhao; Cheng-Wan Li; Jian-Ping Li; Jun-Ming Sun; Rui-Sheng Xu (Molecular Biology Reports, 2012)